Case-control study of risk factors for acute corneal hydrops in keratoconus. Issue 4 (7th July 2016) - Barsam, Allon; Brennan, Nic; Petrushkin, Harry; Xing, Wen; Quartilho, Ana; Bunce, Catey; Foot, Barny; Cartwright, Nathaniel Knox; Haridas, Anjana; Agrawal, Pavi; Suleman, Hanif; Ahmad, Sajjad; et al.
Abstract : Purpose: To determine risk factors for the development of acute corneal hydrops in keratoconus in the UK in a case-controlled study. Methods: Between November 2009 and December 2010, we prospectively identified 73 individuals who developed acute corneal hydrops. We then identified 174 controls from nine regions in the UK with keratoconus who had not had hydrops. For cases and controls we recorded demographics and clinical features. Univariate and multivariable logistic regressions were performed to identify risk factors. Results: Univariate analysis suggested strong associations between the odds of hydrops and each of vernal keratoconjunctivitis (OR 4.08, 95% CI 1.45 to 11.49, p=0.008), asthma (OR 2.70, CI 1.34 to 5.47, p=0.006), atopic dermatitis (OR 3.13, CI 1.50 to 6.56, p=0.002), learning difficulties (OR 7.84, CI 2.86 to 21.46, p<0.001), previous hydrops (OR 40.2; CI 6.2 to ∞, p<0.001), black ethnicity (OR 2.98, CI 0.98 to 8.99; p=0.05), visual acuity in the worse eye (OR 8.76 CI 3.86 to 19.88; p<0.001) and minimum keratometry of ≥48 D prior to the hydrops (OR 4.91, CI 1.07 to 22.6, p=0.041). The use of a contact lens correction was also found to be associated with the odds of hydrops (OR 0.08; CI 0.03 to 0.19, p<0.001). Multiple variable regression indicated that having vernal keratoconjunctivitis (adjusted OR (AOR) 15, 95% CI 1.30 to 173.7; p=0.03), asthma (AOR 4.92, CI 1.22 to 19.78; p=0.025), visual acuity in worse eye (AOR 4.11, CI 1.18 to 14.32; p=0.026) and a high keratometry value (AOR 4.44, CI 0.85 to 23.18; p=0.077) were independently associated with the odds of hydrops in subjects with keratoconus. Conclusion: Some individuals with keratoconus are at high risk of developing acute corneal hydrops. These patients could be managed more aggressively to reduce their risk of developing this complication of their disease.